Estimation of Some Genetic Parameters of Maize Genotypes Affected by Irrigation Intervals - Kazim, Ali Nazim; Fadel Sarheed, Abdullah; H. Romi, Abd-kreem (Journal of Neonatal Surgery, 2025)
A field experiment was conducted during the spring and autumn seasons of 2024 on agricultural land located in the Abu Loka area, Al-Musayyib District, Babil Governorate, Iraq. The land is situated at a latitude of 32⸰ north and a longitude of 44⸰ east, and is approximately 40 km north of the city of Babilon Governorate. The aim was to determine the response of selected maize genotypes to Irrigation intervals for growth traits, yield, and some genetic parameters. The experiment was carried out according to a completely randomized block design with three replicates, using two factors: Irrigation intervals (irrigation every 5 and 10 days), while the second factor included 14 selected genotypes. These were obtained from the spring season and for six genotypes, selection was based on ear length and ear height, which were used as selection indicators. The genotypes used in the spring season were (Fajr, Maha, Baghdad, 5018, American hybrid, Euphrates and HS synthetic variety). The statistical analysis results indicated the following: the 5 day irrigation treatment was superior for the cultivar in all studied traits except for the oil percentage, where the plant yield reached 145.20 g plant-1, the biological yield 463.64 g plant-1, the total yield 7.74 ton ha-1, and the protein percentage 12.05 %. As for the genetic compositions, the genotype (5018), selected using the ear length method, outperformed in most of the studied traits, except for oil content, where it yielded a plant yield of 145.20 g plant-1, a biological yield of 463.64 g plant-1, a total yield of 7.74 ton ha-1, and a protein content of 12.05%.